2021
DOI: 10.14214/sf.10360
|View full text |Cite
|
Sign up to set email alerts
|

Volumes by tree species can be predicted using photogrammetric UAS data, Sentinel-2 images and prior field measurements

Abstract: Photogrammetric point clouds obtained with unmanned aircraft systems (UAS) have emerged as an alternative source of remotely sensed data for small area forest management inventories (FMI). Nonetheless, it is often overlooked that small area FMI require considerable field data in addition to UAS data, to support the modelling of forest attributes. In this study, we propose a method whereby tree volumes by species are predicted with photogrammetric UAS data and Sentinel-2 images, using models fitted with airborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In study III, DIPC data were adjusted horizontally and vertically with ALS data, and DIPC heights were normalized based on ALS DTM. If ALS data are not available, one option is to use DIPC-based DTM in height normalization (Kukkonen et al 2021a). As DIPC-based normalization may perform poorly in areas with a dense canopy, the metrics that are not dependent on the DTM should be studied more in the future (Giannetti et al 2018).…”
Section: Are Als-based Models Transferable To Dipc Data?mentioning
confidence: 99%
See 2 more Smart Citations
“…In study III, DIPC data were adjusted horizontally and vertically with ALS data, and DIPC heights were normalized based on ALS DTM. If ALS data are not available, one option is to use DIPC-based DTM in height normalization (Kukkonen et al 2021a). As DIPC-based normalization may perform poorly in areas with a dense canopy, the metrics that are not dependent on the DTM should be studied more in the future (Giannetti et al 2018).…”
Section: Are Als-based Models Transferable To Dipc Data?mentioning
confidence: 99%
“…One possible option is to use satellite image data in species-specific prediction (Kukkonen et al 2018). Kukkonen et al (2021a) have already demonstrated the use of spectral information from Sentinel-2 images in the prediction of species proportions in DIPC-based forest inventories without new in-situ field measurements. Species proportions were then used to derive the species-specific V predictions.…”
Section: Further Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing has some limitations in assessing forest growth properly. Current remote sensing technologies are rather inefficient for assessing past forest growth, and they have difficulties assessing shares of different tree species [7][8][9].…”
Section: Introductionmentioning
confidence: 99%